3D non‐stationary unmanned aerial vehicles' MIMO channel model. Issue 18 (1st November 2019) - Jia, Haolin; Chen, Hui; Wang, Shiwen; Zhang, Yahong
Abstract : The unmanned aerial vehicle (UAV) channel measurements have shown that the propagation environment of UAV channel is non‐stationary. In this study, a three‐dimensional (3D) non‐stationary UAV multiple‐input multiple‐output (MIMO) channel model is proposed. In order to sufficiently describe the propagation environment of UAV‐MIMO channel, the stationary scatterers and moving scatterers are investigated in the proposed model, which are mimicked using 3D cylinder and two‐dimensional (2D) disc, respectively. The Doppler shifts associated with moving scatterers are also considered in the proposed model. The movement of UAV, receiver, and moving scatterers results in non‐stationarities, and time‐variant distances, azimuth angles, and elevation angles are investigated in the proposed model. The statistical properties of the moving scatterers are also investigated in the proposed channel model. In order to validate the proposed model, the spatial correlation is compared with the measurement results, and the numerical results show that the proposed channel model is applicable to describe the UAV‐MIMO communication systems.